Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Matematis Ditinjau dari Self Regulated Learning Siswa - Musliha Musliha; Rena Revita (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2021)
This research aimed to know the effect of implementing the Problem Based Learning model toward students’ mathematical problem-solving ability derived from their self-regulated learning at MTs Rokan Hulu. This research using a factorial experiment design. By random cluster sampling, 8th-grade students of A-class as the experimental and C-class students as the control group. Data were collected from the mathematical problem-solving ability test and self-regulated learning questionnaire. The result of this study is: 1) there was a difference in mathematical problem-solving ability between students taught by Problem Based Learning model and those who educated by direct learning, 2) there was a difference in mathematical problem-solving ability among students having high, medium and low self-regulated learning, and 3) there was no interaction between Problem Based Learning model and student mathematical problem-solving ability.